Intraclonal diversity of the Pseudomonas aeruginosa cystic fibrosis airway isolates TBCF10839 and TBCF121838: distinct signatures of transcriptome, proteome, metabolome, adherence and pathogenicity despite an almost identical genome sequence. (8th August 2012) - Klockgether, Jens; Miethke, Norbert; Kubesch, Peter; Bohn, Yu‐Sing; Brockhausen, Inka; Cramer, Nina; Eberl, Leo; Greipel, Joachim; Herrmann, Christian; Herrmann, Susanne; Horatzek, Sonja; Lingner, Meike; et al.
Summary Microevolution of closely related Pseudomonas aeruginosa was compared in the clone TB strains TBCF10839 and TBCF121838 which had been isolated from two unrelated individuals with cystic fibrosis who had acquired clone TB during a local outbreak. Compared with the strain PAO1 reference sequence the two clone TB genomes shared 23 155 nucleotide exchanges, 32 out‐of‐frame indels in the coding region and another repertoire of replacement and genomic islands such as PAGI‐1, PAGI‐2, PAGI‐5, LESGI‐1 and LES‐prophage 4. Only TBCF121838 carried a genomic island known from Ralstonia pickettii. Six of the seven strain‐specific sequence variations in the core genome were detected in genes affecting motility, biofilm formation or virulence, i.e. non‐synonymous nucleotide substitutions in mexS, PA3729, PA5017, mifR, a frameshift mutation in pilF (TBCF121838) and an intragenic deletion in pilQ (TBCF10839). Despite their almost identical genome sequence the two strains differed strongly from each other in transcriptome and metabolome profiles, mucin adherence and phagocytosis assays. TBCF121838 was susceptible to killing by neutrophils, but TBCF10839 could grow in leucocytes. Microevolution in P. aeruginosa apparently can generate novel complex traits by few or even single mutations provided that predisposing mutational events had occurred before in the clonal lineage.